Sharia Economic Law Regulation on The Development of Sharia Financial Institutions in Indonesia - Maza, Rina El; Yunarti, Yuyun; Nazeri, Nazeri; Hidayat, Rahmat (Yayasan Sembilan Pemuda Indonesia, 2022)
The analysis of this study aims to provide an objective description and suggest to be able to strengthen and optimize related to the regulation of financial institutions or Islamic banking. In this case, the researcher uses a normative juridical method whose research refers to the rules or regulations of law as reference data which is analyzed with a qualitative description pattern. And the result is that this research illustrates that legal regulations play a role in the development, empowerment and establishment of the regulation of Islamic economic or financial institutions. The implication of study is the creation of progress and synchronization or correlation between financial institutions or Islamic banking in Indonesia. The harmony of regulations and the harmony of legal regulations must have an impact on public trust and have an impact on improving service facilities, protection for the community or customers, economic actors and even Islamic financial institutions themselves.